2021
DOI: 10.3390/ijms222413533
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the Ancestral Tus-Dependent Replication Fork Trap

Abstract: In Escherichia coli, DNA replication termination is orchestrated by two clusters of Ter sites forming a DNA replication fork trap when bound by Tus proteins. The formation of a ‘locked’ Tus–Ter complex is essential for halting incoming DNA replication forks. However, the absence of replication fork arrest at some Ter sites raised questions about their significance. In this study, we examined the genome-wide distribution of Tus and found that only the six innermost Ter sites (TerA–E and G) were significantly bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In a recent study by the Schaeffer lab, ChiP-Seq was used to identify which ter sites are actually occupied by Tus protein. The authors identified ter sites A–E and G ( Figure 1C ), whereas no Tus occupancy was observed at any of the other ter sites ( Toft et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study by the Schaeffer lab, ChiP-Seq was used to identify which ter sites are actually occupied by Tus protein. The authors identified ter sites A–E and G ( Figure 1C ), whereas no Tus occupancy was observed at any of the other ter sites ( Toft et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The highly conserved ter core (6, 8–18) is highlighted by a darker grey. Tus binding ( Toft et al, 2021 ), in vivo fork blocking observed by 2D gel electrophoresis ( Duggin and Bell, 2009 ) and analysis whether a ter site is part of an open reading frame ( Duggin and Bell, 2009 ; Goodall et al, 2021 ) are indicated (see text for further details).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations